Kinetic investigation of the reaction of ethylperoxy radicals with ethanol. Issue 2 (1st October 2020) - Kuzhanthaivelan, S.; Rajakumar, B.
Abstract: The thermodynamic and kinetic investigation for the reaction of ethylperoxy radical (CH3 CH2 OO ) with ethanol (CH3 CH2 OH) was studied computationally with variational transition state theory. The geometry optimization calculations showed that both the reactants have two conformers. The energetics and thermodynamic properties were calculated using the G4 composite method. The results showed that the abstraction of H atom from the ─CH2 ─ site is most feasible, when compared to the other pathways, since it has the lowest energy barrier. The rate coefficient calculations for the title reaction were carried out using the multistructural canonical variational transition state theory with small curvature tunneling corrections in the temperature range of 400‐1500 K. The results showed a similar trend to that of the energetics in which the abstraction of the H atom from the ─CH2 ─ site has a larger rate coefficient, when compared to other reaction pathways. The reactivity trend towards the H atom abstraction by ethylperoxy radicals varies as ─CH2 > ─CH3 > ─OH. The contributions from the ground‐state conformers of both the reactants were included into the total kinetics using the Boltzmann probability distribution. The obtained temperature‐dependent expression for the studied reaction is k total = 1.51 × 10 −32 T 6.3 exp(−3691/ T ) cm 3 molecule −1 s −1 .